A Bibliometric Analysis of Turkish Educational Sciences in the Context of Education and Science Journal - MUHARREM, ALTUNIŞIK; Aktürk, Ahmet Oğuz (Ozgen Korkmaz, 2025)
This study aims to provide a bibliometric overview of the publication and citation trends of the Education and Science Journal (ESJ), one of the most prestigious and longstanding international journals in the field of educational sciences in Türkiye, which has been in publication for 48 years since 1976. The study covers the period from 2007, when ESJ began to be indexed by Web of Science (WoS), to the present day, and it aims to provide researchers with insights and understanding specific to the journal regarding the current status and development of the field of educational sciences in Türkiye. Metadata for a total of 1270 articles published in the journal during this period were obtained from the WoS database. The study includes bibliometric analyses such as the total number of publications and citations, h-index, citations per paper, average number of citations per year, citation thresholds, and total link strength for ESJ between 2007 and 2022. In addition, the study presents visual maps that are generated on the basis of bibliometric mapping analysis conducted using VOSviewer software, including co-authorship, and co-occurrence of author keywords analyses. The results indicate that ESJ has significantly developed over time, enjoys a significant national authorship network, and that in recent years, researchers publishing in ESJ have been focusing on research topics such as action research, mixed methods, meta-analysis, middle school students, social sciences, and mathematical literacy.
Keywords: Bibliometric Analysis; Education and Science; Journal-based Review; VOSviewer; Web of Science